2020
DOI: 10.3758/s13421-020-01017-5
|View full text |Cite
|
Sign up to set email alerts
|

Animacy and threat in recognition memory

Abstract: Animate items are better remembered than inanimate items, suggesting that human memory has evolved to prioritize information related to survival. The proximate mechanisms for the animacy effect are not yet known, but one possibility is that animate items are more likely to capture attention, which then leads to better memory for those items. The first experiment independently manipulated the animacy and perceived threat of studied items and found that both target recognition and false-alarm recognition were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
(110 reference statements)
0
19
1
Order By: Relevance
“…While the animacy effect has robustly been found in free-recall paradigms (Bonin et al, 2014 ; Leding, 2019 ; Meinhardt et al, 2018 , 2020 ; Popp & Serra, 2016 , 2018 ), it is less clear whether there is a robust animacy advantage in recognition paradigms. Some researchers have reported enhanced recognition of animate in comparison to inanimate words (Bonin et al, 2014 ), but inconsistent results have also been obtained (Leding, 2020 ; Mieth et al, 2019 ). For instance, Leding ( 2020 ) reported that animacy induced a guessing bias towards believing the words had occurred before, but the animacy status did not affect memory accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the animacy effect has robustly been found in free-recall paradigms (Bonin et al, 2014 ; Leding, 2019 ; Meinhardt et al, 2018 , 2020 ; Popp & Serra, 2016 , 2018 ), it is less clear whether there is a robust animacy advantage in recognition paradigms. Some researchers have reported enhanced recognition of animate in comparison to inanimate words (Bonin et al, 2014 ), but inconsistent results have also been obtained (Leding, 2020 ; Mieth et al, 2019 ). For instance, Leding ( 2020 ) reported that animacy induced a guessing bias towards believing the words had occurred before, but the animacy status did not affect memory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported enhanced recognition of animate in comparison to inanimate words (Bonin et al, 2014 ), but inconsistent results have also been obtained (Leding, 2020 ; Mieth et al, 2019 ). For instance, Leding ( 2020 ) reported that animacy induced a guessing bias towards believing the words had occurred before, but the animacy status did not affect memory accuracy. A potential reason for these inconsistent findings is that animacy might not equally enhance all processes underlying observable recognition memory performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, researchers examine this effect in the context of the free recall of word lists and have consistently found a recall advantage for animate (e.g., tiger; engineer) over inanimate (e.g., couch; violin) words (e.g., Nairne et al, 2013;Bonin et al, 2014Bonin et al, , 2015Li et al, 2016;Serra, 2016, 2018;Gelin et al, 2017Gelin et al, , 2019VanArsdall et al, 2017;Leding, 2018Leding, , 2019Meinhardt et al, 2018). The advantage can also occur for recognition (Leding, 2020), nonwords given animate properties (VanArsdall et al, 2013), and word pairs (e.g., VanArsdall et al, 2015;DeYoung and Serra, 2021). We do not know the mechanism(s) that underlies the animacy advantage, but researchers have discredited some potential candidates.…”
Section: Introductionmentioning
confidence: 99%
“…The animacy advantage does not seem to occur because animate words are easier to categorize ( Gelin et al, 2017 ; VanArsdall et al, 2017 ), more mentally arousing ( Popp and Serra, 2018 ), more emotionally arousing ( Meinhardt et al, 2018 ), or more threatening ( Leding, 2019 , 2020 ) or invoke greater encoding effort ( Bonin et al, 2015 ; Leding, 2018 ) than inanimate words. At present, there is conflicting evidence whether animate concepts involve greater visual imagery (i.e., Bonin et al, 2015 ; Gelin et al, 2019 ) and conflicting evidence that animate items attract more attention during encoding (i.e., Bonin et al, 2015 ; Hagen et al, 2018 ; Bugaiska et al, 2019 ; Johnson, 2019 ; Leding, 2019 , 2020 ). Growing evidence suggests the effect might stem from the greater richness of encoding for animate items (e.g., Mieth et al, 2019 ; Mah et al, 2020 ; Meinhardt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%